2015
DOI: 10.3748/wjg.v21.i8.2534
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic variceal ligation compared with endoscopic injection sclerotherapy for treatment of esophageal variceal hemorrhage: A meta-analysis

Abstract: Our meta-analysis has found that EVL is better than EIS in terms of the lower rates of rebleeding, complications, and the higher rate of variceal eradication. Therefore, EVL is the first choice for esophageal variceal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
75
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 26 publications
2
75
0
1
Order By: Relevance
“…This underscores the safety of this procedure and agrees with the work of several investigators who demonstrated a higher safety profile of rubber band ligation over sclerotherapy [14][15][16]. The high safety profile in this study may not be unconnected with the fact that prophylactic banding was done in most cases even without bleeding in predominantly in-patients.…”
Section: Discussionsupporting
confidence: 91%
“…This underscores the safety of this procedure and agrees with the work of several investigators who demonstrated a higher safety profile of rubber band ligation over sclerotherapy [14][15][16]. The high safety profile in this study may not be unconnected with the fact that prophylactic banding was done in most cases even without bleeding in predominantly in-patients.…”
Section: Discussionsupporting
confidence: 91%
“…Table 1 summarises the benefits and risks of the therapeutic interventions used in the treatment of duodenal varices. [20][21][22][23][24][25] Our case exemplifies the difficulties of identifying the source of duodenal variceal bleeding. It took four OGDs to locate the source of bleeding and this was possible because of active bleeding at the time of the fourth OGD.…”
Section: Discussionmentioning
confidence: 75%
“…Currently, endoscopic therapy via the obliteration of varices is the first choice of treatment to control variceal bleeding . In China, the two main therapeutic endoscopic modalities that are commonly applied in clinical setting are endoscopic variceal sclerotherapy (EVS) and endoscopic variceal ligation (EVL) . For EVS, a sclerosing agent is injected into the varices to induce vessel thrombosis, which subsequently leads to variceal obliteration .…”
Section: Introductionmentioning
confidence: 99%
“…3 In China, the two main therapeutic endoscopic modalities that are commonly applied in clinical setting are endoscopic variceal sclerotherapy (EVS) and endoscopic variceal ligation (EVL). 4 For EVS, a sclerosing agent is injected into the varices to induce vessel thrombosis, which subsequently leads to variceal obliteration. 5 EVS is effective and relatively inexpensive, and can be easily carried out after training.…”
Section: Introductionmentioning
confidence: 99%